Genome‐Wide Genetic and Transcriptomic Investigation of Variation in Antibody Response to Dietary Antigens. Issue 5 (July 2014) - Rubicz, Rohina; Yolken, Robert; Alaedini, Armin; Drigalenko, Eugene; Charlesworth, Jac C.; Carless, Melanie A.; Severance, Emily G.; Krivogorsky, Bogdana; Dyer, Thomas D.; Kent, Jack W.; Curran, Joanne E.; Johnson, Matthew P.; et al.
ABSTRACT Increased immunoglobulin G (IgG) response to dietary antigens can be associated with gastrointestinal dysfunction and autoimmunity. The underlying processes contributing to these adverse reactions remain largely unknown, and it is likely that genetic factors play a role. Here, we estimate heritability and attempt to localize genetic factors influencing IgG antibody levels against food‐derived antigens using an integrative genomics approach. IgG antibody levels were determined by ELISA in >1, 300 Mexican Americans for the following food antigens: wheat gliadin; bovine casein; and two forms of bovine serum albumin (BSA‐a and BSA‐b). Pedigree‐based variance components methods were used to estimate additive genetic heritability (h2), perform genome‐wide association analyses, and identify transcriptional signatures (based on 19, 858 transcripts from peripheral blood lymphocytes). Heritability estimates were significant for all traits (0.15–0.53), and shared environment (based on shared residency among study participants) was significant for casein (0.09) and BSA‐a (0.33). Genome‐wide significant evidence of association was obtained only for antibody to gliadin (P = 8.57 × 10−8), mapping to the human leukocyte antigen II region, with HLA‐DRA and BTNL2 as the best candidate genes. Lack of association of known celiac disease risk alleles HLA‐DQ2.5 and ‐DQ8 with antigliadin antibodies in the studied population suggests a separate genetic etiology. Significant transcriptional signatures were found for all IgG levels except BSA‐b. These results demonstrate that individual genetic differences contribute to food antigen antibody measures in this population. Further investigations may elucidate the underlying immunological processes involved.